Health Care Quality Through Medical Audit Summary - Piscoya Arbañil, José (2000)
Although inherent in medical task, in last century the patient care quality improvement procedures have achieved a significant development, becoming in cornerstone of an adequate diagnosis and treatment, which gave place to institutionalization of Medical Audit as a speciality within medical practice. Information presented in this review allows clinical history-based sytematic study of medical care process, its diagnosis and treartment guides-contrasted analysis detailinig the historical development, and the choice of unfolding at national context.